Finance and Development, March 1967. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1967)
This paper discusses ways in which countries can invest most profitably in an industry that is capable of providing massive help to their economies. The paper highlights that tourism, like other economic activities, flourishes best when it fits into a context of general economic policies and programs designed to lead to the optimum growth of the economy as a whole. For this, some sort of national planning-at least in setting priorities and seeing that they are emphasized-is required to create a climate for productive investment in all suitable fields.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet